ANALISIS PERHITUNGAN DAN SIMULASI TEGANGAN TWIST LOCK RUBBER TIRED GANTRY CRANE (RTGC) KAPASITAS ANGKAT 35 TON DENGAN MENGGUNAKAN SOFTWARE AUTODESK INVENTOR 2014 - Suryadi Suryadi; Ma'ruf Ma'ruf; Rudi Siswanto (Scientific Journal of Mechanical Engineering Kinematika, 2018)
Rubber Tyred Gantry Crane (RTGC) is a transport lifting equipment which serves to move the containers from head truck to the container terminal or vice versa and as a regulator of the composition of the container stacks. Twist lock is the most important components that are on Rubber Tired Gantry Crane (RTGC). This component is located on the four corners of the spreader. Twist lock function to lock the container at the time of appointment. And load the container will be distributed evenly. This study and simulation to calculate the voltage that occurs at the twist lock with variations in loading and adjusts the nature of the material used. The magnitude of the voltage is done with theoretical calculations and simulated using Autodesk Inventor 2014 software. Based on the research results, the loading of 20 tons, 30 tons and 40 tons with theoretical calculations obtained voltage value is 94705,33 kPa, 142057,98 kPa dan 189410,66 kPa. The simulation results obtained von mises stress value 91900 kPa, 137800 kPa dan 183800 kPa.